Membangun Transparansi dan Akuntabilitas dalam Tata Kelola Sistem Kesehatan Indonesia - Almeria Annisa Putri; Saula Bellatrix Lumbantobing; Riswandy Wasir (Jurnal Ilmiah Kedokteran dan Kesehatan, 2025)
Corruption in the health sector undermines efficiency and reduces the quality of public services. This study aims to analyze the current level of transparency and accountability in Indonesia’s health system governance, identify key challenges, and formulate strategies for improvement. A literature review was conducted using five selected scientific articles from national and international databases published between 2016 and 2025. The findings reveal that weak policy implementation, limited cross-sector coordination, and inadequate understanding of accountability frameworks remain significant barriers. Proposed strategies to improve governance include digitalizing procurement through e-Procurement systems and enhancing community participation in monitoring healthcare services. The adoption of technology-based systems is considered effective in promoting transparency, reducing budget inefficiencies, and strengthening public trust. Therefore, sustainable health governance reform must be supported by improving human resource capacity and increasing health literacy at the community level to build a more transparent, accountable, and responsive health system..